Genome-Wide Identification of R2R3-MYB Transcription Factors Regulating Secondary Cell Wall Thickening in Cotton Fiber Development. (21st December 2018) - Huang, Junfeng; Guo, Yanjun; Sun, Qianwen; Zeng, Wei; Li, Juan; Li, Xuebao; Xu, Wenliang
Abstract: MYB proteins represent one of the largest transcription factor (TF) families in plants, some of which act as key transcriptional regulators of secondary cell wall (SCW) biosynthesis. Cotton ( Gossypium hirsutum ) fiber is thought to be an ideal single-cell model to study cell elongation and SCW biosynthesis. However, little knowledge regarding the TFs controlling fiber SCW biosynthesis, particularly for R2R3-MYBs is known. By far, no comprehensive genome-wide analysis of the secondary wall-associated R2R3-MYBs has been reported in cultivated tetraploid upland cotton. In this study, we identified 419 R2R3-MYB genes by systematically examining the cotton genome. A combination of phylogenetic, RNA-seq and co-expression analyses indicated that 36 R2R3-MYBs were either preferentially or highly expressed in 20 day post anthesis (dpa) fibers and are putative SCW regulators. Among these MYB genes, 22 MYBs are homologs of known SCW MYB proteins and the other 14 MYBs are novel proteins without prior reported SCW biosynthesis-related functions. Finally, we highlighted on the roles of two MYBs named GhMYB46_D13 and GhMYB46_D9, both of which displayed the highest expression in 20 dpa fibers. Expression of GhMYB46_D13 or GhMYB46_D9 individually in Arabidopsis resulted in ectopic SCW deposition in transgenic plants. Furthermore, both GhMYB46_D13 and GhMYB46_D9 were able to activate the cotton fiber SCW cellulose synthase gene promoters. Thus, we have identified 36 R2R3-MYBs as potential SCW regulators in cotton fibers that represent strong candidates for further functional studies during fiber development and SCW thickening.